Functional characterization of biallelic RTTN variants identified in an infant with microcephaly, simplified gyral pattern, pontocerebellar hypoplasia, and seizures. (September 2018) - Wambach, Jennifer; Wegner, Daniel; Yang, Ping; Shinawi, Marwan; Baldridge, Dustin; Betleja, Ewelina; Shimony, Joshua; Spencer, David; Hackett, Brian; Andrews, Marisa; Ferkol, Thomas; Dutcher, Susan; et al.
Abstract Background Biallelic deleterious variants inRTTN, which encodes rotatin, are associated with primary microcephaly, polymicrogyria, seizures, intellectual disability, and primordial dwarfism in human infants. Methods and results We performed exome sequencing of an infant with primary microcephaly, pontocerebellar hypoplasia, and intractable seizures and his healthy, unrelated parents. We cultured the infant's fibroblasts to determine primary ciliary phenotype. Results We identified biallelic variants inRTTN in the affected infant: a novel missense variant and a rare, intronic variant that results in aberrant transcript splicing. Cultured fibroblasts from the infant demonstrated reduced length and number of primary cilia. Conclusion Biallelic variants inRTTN cause primary microcephaly in infants. Functional characterization of primary cilia length and number can be used to determine pathogenicity ofRTTN variants.